Mindfulness Intervention and Nutrition Education for the Prevention of Diabetes Mellitus in Adolescents in Palu City - Fathurahmi F. Rum; Zhanaz Tasya (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Diabetes Mellitus (DM) is a growing public health problem, including among adolescents, due to unhealthy lifestyle changes and high levels of psychosocial stress. Preventing DM in adolescents requires a comprehensive approach that integrates nutritional knowledge, stress management, and mental health. This study aims to analyze the effectiveness of a combined intervention of mindfulness therapy and nutrition education on increasing knowledge, changing attitudes, reducing anxiety levels, and improving blood sugar levels in adolescents in Palu City. Methods: This study used a quasi-experimental design with a pre-test and post-test control group approach. The sample consisted of 60 adolescents aged 15–19 years who were divided into a treatment group (n=30) and a control group (n=30). The treatment group received 8 weeks of mindfulness therapy intervention accompanied by nutrition education, while the control group did not receive mindfulness intervention. Data were collected using knowledge and attitude questionnaires, the Hamilton Rating Scale for Anxiety (HARS) instrument, and blood sugar level measurements. Data analysis was performed using the Wilcoxon test and paired t-test with a significance level of 0.05. Results: Results: Based on the data distribution, the analysis was conducted using the Paired t-test (parametric) and the Wilcoxon test (non-parametric) at ?=0.05. Statistically, there was a significant increase in knowledge (33.3% to 96.6%) and positive attitude (6.7% to 53.3%), as well as a significant change in anxiety levels, namely a decrease in the severe category (33.3% to 10%) and an increase in the normal category (26.6% to 60%). In addition, the proportion of normal blood sugar levels increased from 56.6% to 76.6%, with all changes being statistically significant (p < 0.05). Conclusion: The combined intervention of mindfulness therapy and nutrition education effectively improved knowledge and attitudes, reduced anxiety levels, and improved physiological parameters in adolescents in the prevention of diabetes mellitus. This integrative approach has the potential to become a holistic and sustainable strategy for the promotion and prevention of DM in school-based adolescents.